Icreasing the efficiency of district heating supply systems by local heat distribution station modernation - Yu. A. Gorinov; P. N. Anisimov (Известия высших учебных заведений: Проблемы энергетики)
The PURPOSE of the study is to improve the efficiency of district heating systems. To achieve this purpose, the following tasks must be completed. To consider the problems of functioning of an open heat supply system functioning. Perform an analysis of technical solutions for the modernization of local heat distribution and metering station are presented. To develop a technological scheme of local heat distribution station with a hot-water supply system. To determine the main technical, economic and investment indicators of the developed technical solution.MATERIALS AND METHODS. Measurements were made using the local heat metering station. When solving the set tasks, a methodology for assessing efficiency was applied with the calculation of capital and operating costs, including the calculation of the payback period.RESULTS. A new scheme for regulating of hot water supply system recirculation with open connection of consumers to a centralized source is proposed. The results of the implementation of the developed technical solution of local heat distribution and metering station for apartment buildings in Yoshkar-Ola city are presented. An experimental study of the effect of a joint additional installation of a pump and a control valve on the hot water supply system recirculation line before the mixing unit for hot water recirculation with return pipe and before the direct-acting temperature controller was the first to do. As a result, the consumption of district water was reduced by 36 - 39%, the temperature in the return pipeline was reduced by 13.5%; the enthalpy of the hot water was reduced from 0.168 to 0.145 Gcal/m3, the required circulation in all risers of the hot water supply system was ensured.CONCLUSION. The use of the developed technical solution for the modernization of local heat distribution and metering station increases the efficiency of district heating supply systems. Calculations made on the basis of the readings of automatic custody heat transfer meter showed that the payback period for the technical solution is 40 days. The proposed solution is recommended for use in local heat distribution station of open heat supply system in order to reduce water rate, lower the temperature in the return pipeline and reduce heat losses, improve circulation in all riser pipes of the hot water system.